1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Phosphoprotein whose mRNA is Regulated by the Mitogenic Pathways in Dog Thyroid Cells

Abstract: We have isolated cDNA clones encoding the dog and human forms of a novel protein whose function is still unknown. Sequence analysis indicates that dog clone c5fw protein contains 343 amino acid residues, several potential phosphorylation sites, and two of the 12 conserved subdomains (MI1 and IX) that fold into a common catalytic core structure of the large family of protein kinases. Human clone c S 'shares 95% amino acid identity with its dog counterpart. We have also isolated another human-related clone c53v … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
4
42
1
Order By: Relevance
“…The trbl gene sequence revealed a divergent kinase structure similar to a previously identified cDNA (C5FW, subsequently renamed Trib2) induced by mitogens in dog thyroid cells (Wilkin et al, 1996;Wilkin et al, 1997), indicating that this family of genes is conserved throughout the metazoan lineage. Because fly genes are named after their phenotype, the overproliferating mesodermal cells seen in trbl mutant embryos resembles, as it were, ''Tribbles,'' the fictional small, furry, and fecund animals who vexed the crew of the Enterprise in the classic ''Trouble with Tribbles'' episode from the original Star Trek television series.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The trbl gene sequence revealed a divergent kinase structure similar to a previously identified cDNA (C5FW, subsequently renamed Trib2) induced by mitogens in dog thyroid cells (Wilkin et al, 1996;Wilkin et al, 1997), indicating that this family of genes is conserved throughout the metazoan lineage. Because fly genes are named after their phenotype, the overproliferating mesodermal cells seen in trbl mutant embryos resembles, as it were, ''Tribbles,'' the fictional small, furry, and fecund animals who vexed the crew of the Enterprise in the classic ''Trouble with Tribbles'' episode from the original Star Trek television series.…”
Section: Introductionmentioning
confidence: 65%
“…All three mouse Trib isoforms-Trib1/ C8FW/SKIP1, Trib2/C5FW/SKIP2/ SINK and Trib3/NIPK/SKIP3 (Wilkin et al, 1996(Wilkin et al, , 1997Mayumi-Matsuda et al, 1999)-are reported dispensable for development Yamamoto et al, 2007;Takasato et al, 2008). Trib3 knock-in lacZ expression occurs in the liver and adipose tissues, however, the mutant show neither liver defects, nor a change in the phosphorylation state of Akt .…”
Section: Tribs In Vertebrate Development Mouse Knockouts: Do Overlappmentioning
confidence: 99%
See 1 more Smart Citation
“…In dog thyroid cells, the levels of C5FW protein have been shown to increase upon stimulation with thyrotropin or epidermal growth factor (Wilkin et al, 1997). Expression of neuronal cell death inducible putative kinase (NIPK) is induced when rat neuronal PC6-3 cells are deprived of NGF (MayumiMatsuda et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This molecule contains a serine/threonine kinase catalytic domain but lacks an ATP binding site or one of the conserved catalytic motifs essential for kinase activity. [1][2][3] TRB3 has also been shown to be involved in multiple cellular processes such as glucose/lipid metabolism, muscle/adipocyte differentiation, and stress response by interacting with various functional proteins. 1,[3][4][5][6][7][8][9][10] Three mammalian Tribbles homologues, TRB1, TRB2, and TRB3 are crucial modulators of tumorigenesis.…”
Section: Abstract Tribbles Related Protein 3 (Trb3); Transgenic Mousmentioning
confidence: 99%